FDI Effects To Host Country’s Technological Progress: Evidence From Albanian Manufactoring Industry - Koroci, Aurel; Deshati, Erjona; Sulo, Remzi (European Scientific Journal, ESJ, 2016)
Foreign direct investment (FDI) is perhaps one of the most ambiguous and the least understood concepts in international economics. Common debate on FDI is confounded by several myths regarding its nature and impact on capital accumulation, technological progress, industrialization and growth in emerging and developing economies (Akyüz, 2015). In this circumstance, the purpose of this paper is to explore empirically the impact of Foreign Direct Investment (FDI) on technological progress of Albanian manufacturing industry sectors. We also investigate the effect of FDI on domestic output, namely, whether there is evidence that the inflow of foreign capital crowds out domestic output. Using panel data analysis the empirical part of the paper finds indications that the introduction of FDI has a positive effect on the output of domestic enterprises, that is, FDI has improved the productivity and the technology upgrading of local enterprises.